New N-(3′-acetyl-8-nitro-2, 3-dihydro-1H, 3′H-spiro[quinoline-4, 2′-[1, 3, 4]thiadiazol]-5′-yl) acetamides induced cell death in MCF-7 cells via G2/M phase cell cycle arrest. (21st January 2022) - Shyamsivappan, Selvaraj; Vivek, Raju; Suresh, Thangaraj; Naveen, Palanivel; Kaviyarasu, Adhigaman; Amsaveni, Sundarasamy; Athimoolam, Shunmuganarayanan; Mohan, Palathurai Subramaniam
Abstract : A series of new N -(3′-acetyl-8-nitro-2, 3-dihydro-1 H, 3′ H -spiro[quinoline-4, 2′-[1, 3, 4]thiadiazol]-5′-yl) acetamide derivatives were synthesized from potent 8-nitroquinoline-thiosemicarbazones. Abstract : A series of new N -(3′-acetyl-8-nitro-2, 3-dihydro-1 H, 3′ H -spiro[quinoline-4, 2′-[1, 3, 4]thiadiazol]-5′-yl) acetamide derivatives were synthesized from potent 8-nitroquinoline-thiosemicarbazones. The synthesized compounds were characterized by different spectroscopic studies and single X-ray crystallographic studies. The compounds were assessed for in vitro anticancer properties towards MCF-7 and HeLa cells. The compounds showed superior inhibitory action towards MCF-7 malignant growth cells. Amongst the twelve compounds investigated, compound 4a showed significant inhibitory activity, and the cell death mechanism was evaluated by fluorescent staining, and flow cytometry analyses. The in vitro anticancer results revealed that compound 4a induced cell death by G2/M phase cell cycle arrest. The binding affinity of the compounds with ERα and their pharmacokinetic properties were confirmed by molecular docking studies.